A Analisis Profitabilitas dan Debt to Equity Ratio Sebelum dan Sesudah Akuisisi pada Perusahaan Sektor Energi di Bursa Efek Indonesia - Naysilla Rasya; Assyifatul Jamila; Doli Zulmita; Lusi Ramadhani; Mery Handayani; Yosep Eka Putra; Mega Rahmi (CV. ITTC INDONESIA, 2026)
This study aims to analyze differences in profitability and the debt-to-equity ratio (DER) before and after acquisitions among energy sector companies listed on the Indonesia Stock Exchange during the 2020–2025 period. This study employs a comparative method with a quantitative approach. The research sample was determined using purposive sampling, resulting in 29 companies that met the criteria. The data used consists of secondary data in the form of companies’ financial statements before and after acquisitions. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed Ranks Test because the data were not normally distributed. The results indicate that there was no significant difference in profitability before and after the acquisition, as shown by an Asymp. Sig. (2-tailed) value of 0.792 (>0.05). Furthermore, there was no significant difference in the Debt-to-Equity Ratio (DER) before and after the acquisition, with an Asymp. Sig. (2-tailed) value of 0.964 (>0.05). These findings indicate that acquisition activities in the energy sector have not yet had a significant impact on short-term financial performance. Acquisitions more closely reflect a long-term expansion strategy, the benefits of which are expected to become apparent in subsequent periods.